2015
DOI: 10.5951/teacchilmath.21.9.0548
|View full text |Cite
|
Sign up to set email alerts
|

Three Steps to Mastering Multiplication Facts

Abstract: First understand what fluency is, then use these games and a sequence of strategies to help your students develop facility and confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…We draw on Ulrich's (personal communication) assertion that a child's spontaneous strategy can reveal their number sequence: counting-on reveals the least advanced sequence (INS), doubling reveals the intermediate sequence (TNS), and BAMT reveals the more advanced sequence (ENS). Importantly, this 'mapping' differs from a common expectation that doubling would be most closely related to multiplicative reasoning (Baroody, 2006;Kling & Bay-Williams, 2015;Verschaffel et al, 2007). In contrast to such an expectation, we hypothesize that children who spontaneously employ a BAMT strategy will reason differently and likely outperform students using a doubling strategy (and, of course, counting-on) when solving multiplicative tasks.…”
Section: Theoretical Frameworkmentioning
confidence: 65%
See 1 more Smart Citation
“…We draw on Ulrich's (personal communication) assertion that a child's spontaneous strategy can reveal their number sequence: counting-on reveals the least advanced sequence (INS), doubling reveals the intermediate sequence (TNS), and BAMT reveals the more advanced sequence (ENS). Importantly, this 'mapping' differs from a common expectation that doubling would be most closely related to multiplicative reasoning (Baroody, 2006;Kling & Bay-Williams, 2015;Verschaffel et al, 2007). In contrast to such an expectation, we hypothesize that children who spontaneously employ a BAMT strategy will reason differently and likely outperform students using a doubling strategy (and, of course, counting-on) when solving multiplicative tasks.…”
Section: Theoretical Frameworkmentioning
confidence: 65%
“…While we particularly stress the difference between counting-on and BAMT, we also intend to account for issues surrounding doubling as a commonly-used strategy. Using Carl's example, we emphasize how this strategy, which is often linked with multiplication (Kling & Bay-Williams, 2015), may mask operations on composite units that we distinguish from mDC.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Rather, mathematical fluency and the ability to work facilely with numbers arises from unhurriedly acquiring conceptual knowledge not from anxiously enduring rapid-fire drilling (Boaler, 2014, 2018–2019). Many math educators question whether time-limited testing can even assess, much less develop, fluency (Clarke, Nelson, & Shanley, 2016); some directly deem it ineffectual (Kling & Bay-Williams, 2015), the source of the country’s lackluster mathematical achievement (Flynn, 2017; Pink, 2018), a ritualistic holdover from teachers’ own flawed education (McCloskey, 2014), driven by an erroneous conception of what mathematical skill acquisition is all about (Seeley, 2016). Consequently, the National Council of Teachers of Mathematics (2014) caution against the use of time-limited tests for acquiring or demonstrating mathematical fluency.…”
Section: Further Researchmentioning
confidence: 99%
“…Rather, mathematical fluency and the ability to work facilely with numbers arises from unhurriedly acquiring conceptual knowledge not from anxiously enduring rapid-fire drilling (Boaler, 2014(Boaler, , 2018(Boaler, -2019. Many math educators question whether time-limited testing can even assess, much less develop, fluency (Clarke, Nelson, & Shanley, 2016); some directly deem it ineffectual (Kling & Bay-Williams, 2015), the source of the country's lackluster mathematical achievement (Flynn, 2017;Pink, 2018) Turning to second language instruction, the debate over time-limited versus untimed tests in second language instruction dates as far back as any of the topics we have covered in this article (Carroll & Sapon, 1959, as cited in Carroll, 1990. Even in those earliest days, second language instructors questioned rote drilling as a means for developing fluency (Crawford & Leitzell, 1930, as cited in Nadal, 1950, and researchers demonstrated that fluency was independent of speed (Carroll, 1958).…”
Section: Further Researchmentioning
confidence: 99%
“…However, when the response time is constrained to ensure that participants use retrieval rather than strategies to associate the multiplication problem and its answer [ 11 ] multiplication facts can be learnt the same way that word-pairs are presented in other studies of sleep-related memory consolidation. Indeed, research suggests that rote memorization techniques are frequently used by children to learn multiplication problems as part of a range of strategies [ 12 ]. This raises the potential of leveraging sleep-associated benefits to improve children's multiplication fact knowledge.…”
Section: Introductionmentioning
confidence: 99%